Mechanism of the effect of Mn2+ on the agglomeration and flotation behavior of quartz fines - Qingxia LIANG; Zhihui SHEN; Song MAO; Yunhao YANG; Yue CHENG; Ziqiang CHEN; Liangyu CHEN (工程科学学报, 2025)
Efficient flotation separation of fine rhodochrosite and quartz fines is important for extracting manganese and reducing impurity from fine-grained disseminated manganese carbonate ores. The influence of unavoidable Mn2+ ions released from rhodochrosite particles during fine grinding on the flotation separation of rhodochrosite from quartz should not be ignored. However, there are few researches on the effect of Mn2+ on the flotation of fine rhodochrosite and quartz, especially the effect of Mn2+ on agglomeration and flotation behavior of quartz. In this study, fine quartz was selected as the object. We investigated the mechanism of effect of Mn2+ on the agglomeration and flotation behavior of fine quartz using aggregate properties characterization, micro flotation, adsorption amount measurement, surface properties analysis including contact angle, zeta potential, and chemical state of surface elements, and interparticle interaction energy calculation. The results indicates that the apparent particle size and floatability of quartz are collectively influenced by solution pH, Mn2+ concentration, and sodium oleate dosage. Sodium oleate has no agglomeration and flotation effect on quartz fines, and also cannot change the surface wettability of quartz. However, after the addition of Mn2+ and sodium oleate, the apparent particle size and recovery of quartz increases significantly, as well as the surface hydrophobicity. As Mn2+ and sodium oleate concentration increase, the particle size and recovery ratio of quartz first increase and then decrease. However, the agglomerates redispersed at high Mn2+ and sodium oleate concentrations. In a weakly alkaline environment, Mn2+ has a significant activating effect on both the agglomeration and flotation of quartz, with the optimal activation pH being 10. When the concentrations of Mn2+ and sodium oleate are both 1×10–2 mol·L1 and the pH is 10, the average particle size (Dmean) of quartz agglomerates is greater than 50 μm, along with the volume fraction of 30–100 μm size fraction of greater than 50% and recovery ratio of greater than 87%. In addition, the monolayer adsorption density of sodium oleate on the quartz surface is larger, resulting in the higher hydrophobic. Mn2+ can be adsorbed on the quartz surface through electrostatic attraction, providing active sites (—Si—O—Mn+) for sodium oleate adsorption and inducing hydrophobic modification of quartz. Furthermore, under weakly alkaline conditions, Mn(OH)+ and \begin{document}$ M{{n}_2}(OH)_3^ + $\end{document} interact with RCOO– and \begin{document}$ \left( RCOO \right)_2^{2 - } $\end{document}, forming strong hydrophobic interactions on the quartz surface through both physical and chemical adsorption. These hydrophobic interactions can overcome the electrostatic repulsion, thereby promoting agglomeration and flotation of quartz. However, in the strong alkaline environment, Mn2+ loses its activating effect on quartz, and the quartz recovery decreases significantly, mainly due to the consumption of a large amount of Mn2+ by the precipitation of Mn(OH)2, which results in the quartz surface becoming hydrophilic again. Therefore, regulating the pulp environment to be weakly acidic can avoid the activation of quartz by Mn2+ with sodium oleate, which is conducive to the selective agglomeration and flotation separation of rhodochrosite and quartz. The research results are of great theoretical significance for the regulation of enhanced flotation of fine rhodochrosite and quartz, as well as the extraction of manganese and reduction of impurities from fine-grained disseminated manganese carbonate ores.